Research on Wi-Fi HaLow for the Internet of things - Le TIAN; Yuxiang HU; Weitao HAN (物联网学报)
The new Wi-Fi standard,named IEEE~802.11ah or Wi-Fi HaLow,is considered as a very promising technology for the Internet of things (IoT),aiming to support large-scale IoT networks in an energy-efficient manner.It is mainly to be used for IoT scenarios,such as smart homes,digital health care,connected cars,industrial process control,logistics ＆amp;asset management,smart cities,agriculture ＆amp; environmental sensors,etc.An overview of the IEEE 802.11ah technology and its recent development were provided.The key features were explored,demonstrating that IEEE 802.11ah is suitable for its target use cases.Moreover,a comprehensive summary and analysis of the related work were conducted.Finally,identifies several open research issues that need to be addressed to fully realize the vision of large-scale and low power Wi-Fi networks for the IoT were discussed.